Mechanisms for Assessing the Quality of Education in Kazakhstan (Journal of Educational Sciences, 2019)
It was studied the issues of assessing the quality of higher education in Kazakhstan in the article. The history of the transition from intermediate state control (ISC) to an external assessment of academic achievement (EAAA) in assessing the quality of higher education in Kazakhstan was studied and analyzed. The tasks, stages and results of the intermediate state control (ISC) and the external assessment of academic achievement (EAAA) are considered. In a comparative aspect, the characteristic features of the ISC and EAAA are analyzed in assessing the quality of the organization of the educational process and monitoring the quality of education. Comparative characteristics of educational achievement assessment methods are given. Attention is focused on the qualitative differences between these monitoring systems: a slice and evaluation of the process in the middle of the educational path and the resulting external assessment of students’ achievements as information for the Kazakhstani public, stimulating the competition of universities, stimulating the activities of educational organizations to improve the quality of services provided; bias from the assessment of compulsory disciplines to the basic and core disciplines. At the same time, the authors substantiate the current changes in the VOUD system – the transition to the assessment of general educational disciplines from 2019. Key words: monitoring the quality of education, intermediate state control, external assessment of academic achievements, clustering.